Gagasan Pelestarian Gedung Singa di Kota Surabaya melalui Revitalisasi - Arifin, Muhammad Haris; Savitri, Mimi (PURBAWIDYA, 2024)
An abandoned heritage building that was built in 1901, known as Gedung Singa in the city of Surabaya, was listed for auction and the plan had raised protests from the heritage activists community. This concern was emanated by previous cases of demolition of protected heritage buildings as happened to Toko NAM, which are lamented by the heritage activists community who have become a major contributor in the effort of safeguarding heritage, including listed heritage objects. This shows the urgency of negotiating Gedung Singa’s significance to the people and of proposing an appropriate form of revitalization as to assure its sustainable preservation. This study uses exploratory literature study method and approaches the issue by using a theory known as Interaction Field Model. The result proposes a plan to turn Gedung Singa into a museum-restaurant showcasing returned heritage collections from the Netherlands as a way to strengthen the image of Surabaya as the city of heroes. Other collections that may be displayed are chosen objects in accordance to the thematic exhibitions which are arranged temporarily to accommodate interactions with the people.